Important contributions of non-fossil fuel nitrogen oxides emissions - Wei Song (Nature Portfolio, 2021)
This study investigates in the importance of non-fossil fuel NOx emissions in the surface-earth-nitrogen cycle. The study shows how changes of regional human activities directly influence δ15N signatures of deposited NOx to terrestrial environments and that emissions have largely been underestimated.